Socially Anxious Tendencies Affect Impressions of Others’ Positive and Negative Emotional Gazes - Tsuji, Yuki; Shimada, Sotaro (Frontiers in Psychology, 2018)
Socially anxious tendencies have potential to become social anxiety disorder, which is characterized by fear of social situations associated with being evaluated or embarrassed by others. In particular, others’ gazes induce social anxiety. People with social anxiety disorder have a negative interpretation bias toward ambiguous emotions in others’ faces; however, negative interpretation bias toward ambiguous emotions in others’ gazes has not been fully investigated. We used an impression judgment task to examine negative interpretation bias toward others’ gazes among people with socially anxious tendencies. We generated emotionally ambiguous gazes (positive, negative, and neutral) using a morphing technique with 10% steps (neutral, 10%–100% negative, and 10%–100% positive). Participants (all male) were asked to judge whether the stimulus was positive or negative. Each participant’s level of social anxiety was examined using the Japanese version of the Social Phobia Inventory (SPIN-J), which measures three symptom dimensions: fear, avoidance, and physiological arousal. To examine the influence of socially anxious tendencies in the impression judgment task, we calculated the point of subjective equality (PSE) using a two-step logistic curve fitted to individual participant’s responses. The negative emotional intensity of the PSE became lower as the fear score became higher (p < .05). This result suggests individuals with a high tendency towards social anxiety tend to interpret subtle negative emotional gazes as a negative emotion and regard these gazes as a threat.